RE-DESAIN SEKOLAH (DASAR) PASCA PANDEMI COVID - Gergy Hardian Wienaldi (Jurusan Arsitektur dan Perencanaan, 2021)
In order for reducing the epidemic Covid-19, government issued policies such as physical distancing, social distancing, and large-scale social editing (PSBB). This condition requires people to limit their activities, to stay at home, to study, work, and limit their activities at home. The education sector such as schools need to adjust the learning process gradually, directly into bold learning that can be done in the homes of individual students. This policy has a negative impact due to the implementation of the learning process at home where the learning time limit is not clear. Teachers and students experience various disturbances in the learning process such as limited tools, lack of communication, and readiness to face the online learning process. Which has an impact on children's psychological, decreasing the quality of children's skills to reduce socialization. Post-Covid Pandemic Schools is a project designed how schools adapt to this situation. Schools with social distancing protocols in classrooms and their environment, new student-centered learning methods, namely student-centered learning systems and teachers as their companions. This project is expected to provide a safe and comfortable place to study in the conditions of the Covid-19 pandemic. The school will aim at Education 4.0, namely the school of flexibility and creativity, across fields remotely for learners. Keywords: Online Learning; Covid Pandemic; Education 4.0 ; Social Distancing ABSTRAKSebagai upaya untuk mengurangi penyebaran virus Covid-19, pemerintah mengeluarkan kebijakan seperti physical distancing, social distancing, hingga pembatasan social berskala besar (PSBB). Kondisi ini mengharuskan masyarakat untuk membatasi aktivitasnya yaitu untuk tetap di rumah, belajar, bekerja, dan beribadah di rumah. Sektor pendidikan seperti sekolah perlu menyesuaikan proses pembelajarannya yaitu dari secara tatap muka langsung menjadi pembelajaran secara daring yang bisa dilakukan di rumah masing-masing siswa. Kebijakan ini menimbulkan beberapa dampak negative karena penerapan proses pembelajaran di rumah yang tidak jelasnya batas waktu belajar. Guru dan siswa mengalami berbagai gangguan dalam proses belajar seperti keterbatasan alat, berkurangnya komunikasi, serta kesiapan menghadapi proses pembelajaran online. Yang berdampak pada psikologis anak, menurunnya kualitas keterampilan anak hingga berkurangnya sosialisasi. Sekolah Pasca Pandemi Covid adalah sebuah proyek yang dirancang bagaimana sekolah beradaptasi menghadapi situasi ini. Sekolah yang menjalan protokol social distancing pada kelas dan lingkungannya, metode pembelajaran yang baru student-centered learning yaitu sistem pembelajaran yang berpusat kepada murid dan guru sebagai pendampingnya. Proyek ini diharapkan bisa menyediakan tempat belajar yang aman dan nyaman disaat kondisi pandemic Covid-19. Sekolah akan kearah Edukasi 4.0 yaitu fleksibilitas dan kretivitas, lintas bidang secara jarak jauh untuk pembelajar sekolah.